Evaluation of Sodium Chloride and Acidity Effect on Corrosion of Buried Carbon Steel Pipeline in Iraqi Soil - Sulaiman, Qasim; Al – Taie, Ali; Hassan, Dahlia Mohamed; and Industrial Development, Commission of Research (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
In this work, corrosion parameters were evaluated using potentiodynamic polarization curves. In order to determine corrosion parameters of potential and current density of the interesting metal, carbon steel, environmental conditions of external corrosion of buried carbon steel pipeline in Iraqi soil were prepared in the laboratory using simulated prepared conditions. Solutions of sodium chloride at different concentrations (300, 1100, 1900, 2700, and 3500 ppm) were used. pH of solution were acidic at pH =5, and alkaline at pH = 9. Laboratory conditions were similar to those of Iraqi soil where the pipelines were buried. Temperature was constant at 20 °C. Potentiodynamic polarization curves, of potential vs. log current density, were obtained using M Lab Multi-Channel Potentiostat/Galvanostat. The carbon steel coupon (ASTM A179-84A) was used as the studied metal. The results of this work reveal the behavior of carbon steel in external corrosion conditions under Iraqi soil. The rate of corrosion, of carbon steel, increases with the increase in chloride concentration in solution. As pH changes from acidic to alkaline medium, the rate of corrosion decreases.